2014
DOI: 10.3390/s140610177
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing Activity in Pandoraea pnomenusa RB38

Abstract: Strain RB38 was recovered from a former dumping area in Malaysia. MALDI-TOF mass spectrometry and genomic analysis identified strain RB-38 as Pandoraea pnomenusa. Various biosensors confirmed its quorum sensing properties. High resolution triple quadrupole liquid chromatography–mass spectrometry analysis was subsequently used to characterize the N-acyl homoserine lactone production profile of P. pnomenusa strain RB38, which validated that this isolate produced N-octanoyl homoserine lactone as a quorum sensing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…However, isolate identification performed in a previous study using 16S rDNA sequencing and Matrix-assisted Laser Desorption Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS) identified strain RB38 as P . pnomenusa ( Ee et al, 2014b ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, isolate identification performed in a previous study using 16S rDNA sequencing and Matrix-assisted Laser Desorption Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS) identified strain RB38 as P . pnomenusa ( Ee et al, 2014b ).…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported the QS activity of P. pnomenusa RB38 ( Ee et al, 2014b ). In this study, we identified the putative luxI and luxR 1 homologs from the annotated genome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Members of genus Pandoraea have been reported with QS activity and are able to communicate via the production of AHLs (Ee et al, 2014). In this study, we investigated (1) if AHL-mediated QS is a common activity employed by all type strains of Pandoraea species and (2) the distribution of QS genes in Pandoraea genus.…”
Section: Introductionmentioning
confidence: 99%
“…In the fourth cycle, 50 µl of enriched KGm medium was plated on KGm agar, and colonies of bacteria with distinctive morphology were isolated and streaked until a single colony was obtained. Strain RB-25 T was selected for further analysis as it activated a CV026 biosensor and it was routinely cultivated at 28 C in Luria-Bertani (LB) media (Ee et al, 2014b;Lim et al, 2014;McClean et al, 1997). Colonies of strain RB-25 T were slightly raised with very pale white pigmentation on LB medium after 24 h of incubation.…”
mentioning
confidence: 99%